PENGARUH PERANAN GURU AKIDAH AKHLAK DALAM PEMBENTUKAN AKHLAKUL KARIMAH SISWA: Volume 1, Nomor 1 (2024) - Ahmadiy Al Manulhaq (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the activities of moral aqidah teachers in the formation of students' akhlakul karimah. This type of research is descriptive qualitative in nature. Data sources in this research are primary and secondary data sources. The data collection techniques used are observation, interviews and documentation, the validity of the data used is the data source, while the data analysis used in this research is data presentation, data reduction and drawing conclusions or conclusions. The results of this research are that the activities of the Aqidah Akhlak teacher have an important role in improving students' morals. Teachers as role models play an active role in forming positive attitudes, behavior and Islamic values ​​through interactive teaching methods, role models and a fun approach. Apart from that, Aqidah Akhlak teachers also play an important role in integrating religious teachings with students' daily lives. They guide students in facing moral situations and challenges, provide an understanding of the importance of akhlakul karimah, and provide guidance and learning of Islamic moral values.